Answer:
g(b) = 3b +13
Step-by-step explanation:
Effectively, you want to solve for "a".
a-7 = 3(b+2)
a = 3b +6 + 7 . . . . . . eliminate parentheses, add 7
g(b) = 3b +13
Answer: 3b +13
Step-by-step explanation:
Answer:
G'(-4, -3)
G'(3, 4)
G'(-8, 6)
Step-by-step explanation:
Coordinates of the original point G on the graph → (-4, 3)
When the point G is reflected over the x-axis,
Rule to be followed fro the reflection,
(x, y) → (x, -y)
By this rule image of the point G will be,
G(-4, 3) → G'(-4, -3)
Rule for the rotation by 90° clockwise,
(x, y) → (y, -x)
G(-4, 3) → G'(3, 4)
Rule for the translation of 4 units left and 3 units up,
(x, y) → [(x - 4), (y + 3)]
G(-4, 3) → [(-4 - 4), (3 + 3)]
→ (-8, 6)
HELP!!!!
Answer:-69
Step-by-step explanation:-85 - -16 would be changed to -85+16 because there are two minus signs next to eachother.
Answer:
y = 1/3x+6
Step-by-step explanation:
Step 1
- Rewrite f(x) as y
f(x) = 3x-18 => y = 3x-18
Step 2
- Swap x and y
y = 3x-18 => x = 3y-18
Step 3
- Slove for y (By that it means isolate y)
x = 3y-18 (+18 both sides)
x+18 = 3y (Then divide both sides by 3)
1/3x+6 = y
Final Answer:
y = 1/3x+6